Experiencing Art: The Influence of Expertise and Painting Abstraction Level - Pihko, Elina; Virtanen, Anne; Saarinen, Veli-Matti; Pannasch, Sebastian; Hirvenkari, Lotta; Tossavainen, Timo; Haapala, Arto; Hari, Riitta (Frontiers in Human Neuroscience, 2011)
How does expertise influence the perception of representational and abstract paintings? We asked 20 experts on art history and 20 laypersons to explore and evaluate a series of paintings ranging in style from representational to abstract in five categories. We compared subjective aesthetic judgments and emotional evaluations, gaze patterns, and electrodermal reactivity between the two groups of participants. The level of abstraction affected aesthetic judgments and emotional valence ratings of the laypersons but had no effect on the opinions of the experts: the laypersons’ aesthetic and emotional ratings were highest for representational paintings and lowest for abstract paintings, whereas the opinions of the experts were independent of the abstraction level. The gaze patterns of both groups changed as the level of abstraction increased: the number of fixations and the length of the scanpaths increased while the duration of the fixations decreased. The viewing strategies—reflected in the target, location and path of the fixations—however indicated that experts and laypersons paid attention to different aspects of the paintings. The electrodermal reactivity did not vary according to the level of abstraction in either group but expertise was reflected in weaker responses, compared with laypersons, to information received about the paintings.